2020
DOI: 10.1002/rcm.8989
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous screening of dietary supplements for 25 anti‐hyperlipidemic substances using ultra‐performance liquid chromatography and liquid chromatography/electrospray ionization tandem mass spectrometry

Abstract: RationaleRecently, illegal dietary supplements containing unauthorized compounds have been seized and internationally publicized with a warning to avoid their consumption. This adulteration can be a serious threat to public health because of insufficient and reliable safety data as well as their undesirable side effects. It is, therefore, essential to rapidly and accurately develop and simultaneously validate analytical methods for these unauthorized anti‐hyperlipidemic substances.MethodsDietary supplements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, it has been often reported that unauthorized compounds, including steroids and selective androgen receptor modulators (SARMs), are illegally adulterated in dietary supplements that are distributed via overseas direct purchases and purchasing agents. [1][2][3] Steroids and SARMs are hormone modulators that directly occur during critical physiological processes such as endocrine development, reproduction and metabolism. Moreover, an incorrect dose of such substances can cause side effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been often reported that unauthorized compounds, including steroids and selective androgen receptor modulators (SARMs), are illegally adulterated in dietary supplements that are distributed via overseas direct purchases and purchasing agents. [1][2][3] Steroids and SARMs are hormone modulators that directly occur during critical physiological processes such as endocrine development, reproduction and metabolism. Moreover, an incorrect dose of such substances can cause side effects.…”
Section: Introductionmentioning
confidence: 99%
“…2019 Rapid detection of adulteration of dehydroepiandrosterone in slimming products by competitive indirect enzyme-linked immunosorbent assay and lateral flow immunochromatography [ 832 ]; screening method for detection of illegal adulterants in ginseng pills by profiling analysis of HPLC multi-dimensional fingerprints [ 833 ]; 2020 identification of tert-butyl-4-anilinopiperidine-1-carboxylate (4-anilinopiperdine-t-BOC or 4-AP-t-BOC) in seized falsified ‘Xanax’ tablets and suspected heroin seizures [ 834 ]; 20 herbal mixtures containing Cumyl-PEGACLONE were quantitatively analyzed by HPLC-DAD after an initial screening by gas chromatography mass spectrometry [ 835 ]; simultaneous and reliable determination of 20 pharmaceutical compounds in adulterated health food products using liquid chromatography with electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) and liquid chromatography with quadrupole-time-of-flight mass spectrometry (LC-QTOF-MS) [ 836 ]; MALDI-MS method for analysis of illegal drugs and doped substances added in supplements [ 837 ]; 2021 voltammetric method for analyzing weight loss products adulterated amphetamine [ 838 ]; development and validation of an HPLC-MS/MS system for the analysis of 16 chemical drugs illegally added to dietary supplements for weight-loss in a capsule form [ 839 ]; quantification of pharmaceuticals or prescription medications (fluoxetine, phenolphthalein, and sibutramine illegally added to herbal weight loss supplements by RP-HPLC-MS/MS [ 840 ]; IMS qualitiative screening method for illicit additives (ibuprofen, nitrazepam, nitrendipine, indomethacin, phenobarbital, sibutramine, diclofenac sodium, diazepam, estazolam, melatonin, phenolphthalein, prednisone acetate, betamethasone, metformin HCl, glibenclamide, and tadalafil) in herbal pharmaceuticals and health foods with quantification by HPLC [ 841 ]; UPLC-PDA and LC/EIS-MS/MS methods for simultaneously screening for 25 anti-hyperlipidemic substances illegally added to dietary supplements [ 842 ]; HPLC-DAD method for the identification and quantification of sexual stimulants and anabolic steroids in the adulterated dietary supplements [ 843 ]; MALDI-MS method for the analysis of illegally added and doped substances added to medicines or food [ 837 ]; 2022 mixed-mode sorbent for SPE of hydrophobic and hydrophilic illegal additives from food sample followed by analysis by RPLC/HILIC-MS/MS [ 844 ]; analytical techniques and metrological principles in studying dietary supplement products and ingredients, particularly medicinal plants and other botanicals [ 845 ]; a membrane-protected micro-SPE method based on molecular imprinting and its application to the determination of local anesthetics illegally added to cosmetics [ 846 ]; application of predicted fragmentation pathways and fragment ion structures with LC-QTOF-MS for the analysis of 15 steroids and 20 selective androgen receptor modulators in dietary supplements [ 847 ]; development of an atmospheric pressure solids analysis probe coupled with single-quadrupole mass spectrometer (A...…”
Section: Instrument Focusmentioning
confidence: 99%
“…In studies of dietary supplements, these types of spectrometers are often combined with a liquid chromatograph (LC–MS/MS). They are frequently used for the analysis of dietary supplements supporting weight loss and for physically active people, usually in the form of stimulants and substances with anorexic, diuretic, or laxative effects [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%